Konsep MujᾹdalah dalam Al-Qur’an Kontekstualisasi Klasik dan Kontemporer (Kajian terhadap Ayat-ayat Jadal) - Khairani, Dwi (ANWARUL, 2024)
This thesis discusses the concept of Mujādalah in the Al-Qur'an in classical and contemporary times. The problem that is the focus of this thesis research is that the author clearly explains the concept of mujādalah in classical and contemporary times, including several verses that discuss the concept of mujjadilah as well as the opinions of several mufassirs regarding the concept of mujādalah. That's why the author raised it as a scientific research. The method used in this research is descriptive analysis method. By using the Al-Qur'an, source books, and books of interpretation. As supporting data and comparative data, the author presents the works of scholars in this thesis. This research was conducted with the aim of knowing the concept and ethics of implementing mujjadi according to the Koran and its effectiveness as a method of da'wah. The existence of Islamic da'wah nowadays has a very static understanding among the majority of society. If it is said to be da'wah when there is a speaker, the means and material presented are full of humor or have lots of jokes in it. Meanwhile, when someone presents material, of course the material in question is more focused on certain areas and issues, but the majority of people tend not to want to listen or are even completely indifferent. The classical and modern views of da'wah should be synchronized again, so that the targets and objectives of da'wah are in the context of how the material presented can be reached and accepted by society, so that change in society as the final target is achieved.